Bragg Solitons – Historical and Future Perspectives - Tan, Dawn T. H.; Eggleton, Benjamin J. (Laser & photonics reviews, 2023)
Solitons have been a subject of intense intellectual curiosity and an avenue for a plethora of applications since they are first observed in water waves. Optical solitons, in particular, have seen tremendous progress, starting from their first theoretical predictions in optical fiber in 1973. On the 50th anniversary of this seminal work from Haseagawa and Tappert, a review is provided on the progress in an important class of optical solitons, the Bragg soliton. Bragg solitons are optical solitons which exist in structures periodic in one dimension. The history of Bragg solitons is described, including the most salient advancements made both in theory and experiments. Recent progress made in integrated photonic devices and their associated design advantages are highlighted, with particular emphasis on how these have facilitated the realization of Bragg soliton dynamics on a chip and their optical processing functions. A discussion and future outlook for this burgeoning field provides a perspective on how Bragg solitons may impact the field of photonics and future applications. On the 50th anniversary of Haseagawa and Tappert's first theoretical predictions of solitons in fiber, the progress in an important class of optical solitons, the Bragg soliton, is reviewed. The history of Bragg solitons and recent progress made in Bragg soliton dynamics on a chip are covered, and perspectives are provided on how they may impact the field of photonics and future applications.